2014
DOI: 10.1016/j.jmau.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative light and electron microscopic studies of dorsal skin melanophores of Indian toad, Bufo melanostictus

Abstract: a b s t r a c tIndian toad, Bufo melanostictus is an amphibian, which is able to change the body color to adapt to its ambient need. This ability is due to specialized skin pigment cells known as melanophores which are excellent animal-cell models to study most of the physiological phenomenon related to color changes. In the present investigation morpho-anatomic details of dorsal skin melanophores of B. melanostictus were studied by means of light and electron microscope to establish their phylogenetic relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Colour change in D. melanostictus works exclusively via large melanophores in the sub-epidermis, as individuals have no other chromatophores (xanthophores, erythrophores) [ 43 ]. In other anurans, dispersion of yellow pigments in xanthophores and aggregation of dark pigments in melanophores underlies yellow and orange colour [ 21 , 22 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colour change in D. melanostictus works exclusively via large melanophores in the sub-epidermis, as individuals have no other chromatophores (xanthophores, erythrophores) [ 43 ]. In other anurans, dispersion of yellow pigments in xanthophores and aggregation of dark pigments in melanophores underlies yellow and orange colour [ 21 , 22 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…All four dorsal fins were fixed overnight in a 0.01 M phosphate buffer solution (PBS) containing 4% paraformaldehyde (PFA) and 2.5% glutaraldehyde (GA) before being transferred to a PBS solution with a pH ranging from 7.2 to 7.4. Such fixation protocols are widespread in the scientific literature for histological observations of melanosomes in biological organisms, including fish [26][27][28][29][30]. Ideally, our study should have been carried out with fresh or living tissues.…”
Section: Sample Preparation and Treatmentmentioning
confidence: 99%
“…As lower vertebrates share similar mechanism of skin pigmentation with human beings, they have outstanding potential as phylogenetical tools to demystify and better understand their role in pigmentation biology and its evolutionary significance. Several detailed elucidations have been done on the fine structure of melanophores of various classes of vertebrates like teleosts and lung fishes [36][37][38], larval amphibians, Indian toad [39], and reptiles [40], which have revealed remarkably consistent fine structural features of these melanosomes synthesizing cells in order to explain their role in color changes. In the cytoplasm of the epidermal and sub-epidermal melanophores, well developed nucleus, tubular type of vesicular mitochondria, Golgi body, vesicular endoplasmic reticulum with oval to elliptical melanosomes of various degree of melanization have been found to remain randomly scattered [39], resembling similar ultrastructural features of mammalian melanocytes.…”
Section: Stage IImentioning
confidence: 99%
“…Several detailed elucidations have been done on the fine structure of melanophores of various classes of vertebrates like teleosts and lung fishes [36][37][38], larval amphibians, Indian toad [39], and reptiles [40], which have revealed remarkably consistent fine structural features of these melanosomes synthesizing cells in order to explain their role in color changes. In the cytoplasm of the epidermal and sub-epidermal melanophores, well developed nucleus, tubular type of vesicular mitochondria, Golgi body, vesicular endoplasmic reticulum with oval to elliptical melanosomes of various degree of melanization have been found to remain randomly scattered [39], resembling similar ultrastructural features of mammalian melanocytes. From these studies it is concluded that the presence of immature, pre-melanosomes to highly electron dense, mature melanosomes showing progressive degrees of melanization from stage I to stage IV melanosomes, in lower vertebrate melanophores is similar to mammalian melanocytes with same mode of development [41,42].…”
Section: Stage IImentioning
confidence: 99%